2012
DOI: 10.1007/s12070-012-0523-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Enucleation and Chemical Cauterization (Carnoy’s) in the Management of Odontogenic Keratocyst of the Jaws

Abstract: The purpose of this study was to evaluate the use of enucleation and chemical cauterization in the management of odontogenic keratocyst (OKC) of the jaw. This study involves the retrospective review of 32 patients (20 males and 12 females) with 34 biopsy proven odontogenic keratocysts. All patients received a combination of enucleation and chemical cauterization with every time freshly prepared Carnoy's solution (absolute alcohol 6 mL, chloroform 3 mL, glacial acetic acid 1 mL, ferric chloride 0.1 gm/mL). None… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
(14 reference statements)
0
12
0
1
Order By: Relevance
“…The main results of the included clinical studies are shown in Table 2. It should be noted that the studies performed by Zhao et al (14) and Rao and Kumar (37) did not clearly specify the presence of the parakeratotic component.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The main results of the included clinical studies are shown in Table 2. It should be noted that the studies performed by Zhao et al (14) and Rao and Kumar (37) did not clearly specify the presence of the parakeratotic component.…”
Section: Resultsmentioning
confidence: 92%
“…High recurrence rates have been described for this lesion (4,5,9,12,14,37) mainly depending on the treatment modality (3,7). Accordingly, a recently published study (40) quantified Cyclin D1 (CCD1) expression levels, a nuclear protein essential for cell cycle progression, in a series of keratin-producing odontogenic cysts.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Tanto na prática como na teoria, é quase unânime que a aplique, por meio de gaze ou algodão embebido, diretamente sobre o leito ósseo após a remoção de determinada lesão. Contudo, ainda há frequente disparidade de opiniões em relação ao tempo dessa aplicação, girando em torno de 1 minuto (Rao;Kumar, 2014); 3 minutos (Williams;Connor, 1994;Blanas et al, 2000;Lee et al, 2004;Ribeiro Junior et al, 2012;Rajeshkumar et al, 2013); um pouco mais de 3 minutos (Frerich et al, 1994) e 5 minutos Bronkhorst, 1988;Saulacic et al, 2009 (Pereira et al, 2015;Dias et al, 2016 ocorreram nos casos em que a primeira cirurgia foi em região dentada e a presença das raízes dificultaram o acesso a toda lesão.…”
Section: Introductionunclassified